Isolation and characterisation of Vibrio harveyi as etiological agent of foot pustule disease in the abalone Haliotis discus hannai Ino 1953 - Wang, R. X.; Yao, T.; Liu, X. J.; Wang, J. Y. (Indian Journal of Fisheries, 2018)
Foot pustule disease is an important disease affecting abalones. In the present study, microbiological and histopathological investigations were carried out in the Japanese abalone Haliotis discus hannai, affected by foot pustule disease. Diseased abalones became lethargic, weak, and eventually died. The remarkable symptoms were apparent foot pustules and atrophy of the foot muscle. A predominant bacterium designated as BV2 was isolated from the pustules of diseased abalones. Experimental infection by immersion challenge showed that BV2 was virulent to abalones and caused symptoms of foot pustule disease with median lethal dose value of â‰ˆ7.76Ã—105 cfu ml-1. BV2 was infectious to all tested abalones with high mortality. Histopathological investigations showed degeneration and collapse of foot muscles as well as connective tissues. Tissues in round pustules were necrotic and disorganised. The BV2 bacterium was identified as Vibrio harveyi based on the results of phenotypic and biochemical tests as well as 16S rRNA gene sequence analysis.. The bacterium was found resistant to kanamycin and clindamycin, and sensitive to other 11 antibiotics tested.